2022
DOI: 10.1186/s12910-022-00767-y
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on returning individual and aggregate genomic research results to study participants and communities in Kenya: a qualitative study

Abstract: Background A fundamental ethical challenge in conducting genomics research is the question of what and how individual level genetic findings and aggregate genomic results should be conveyed to research participants and communities. This is within the context of minimal guidance, policies, and experiences, particularly in Africa. The aim of this study was to explore the perspectives of key stakeholders' on returning genomics research results to participants in Kenya. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 79 publications
1
3
0
Order By: Relevance
“…Research teams should select an approach that is creative, flexible and sensitive to participants’ values, beliefs and education levels. Their views are consistent with a study that explored perspectives on returning individual and aggregate genomic research results to study participants and communities in Kenya [ 55 ]. Researchers suggested using music, dance and drama as an approach that could enhance communication of understandable information about pharmacogenomic research and results at community level.…”
Section: Discussionsupporting
confidence: 81%
“…Research teams should select an approach that is creative, flexible and sensitive to participants’ values, beliefs and education levels. Their views are consistent with a study that explored perspectives on returning individual and aggregate genomic research results to study participants and communities in Kenya [ 55 ]. Researchers suggested using music, dance and drama as an approach that could enhance communication of understandable information about pharmacogenomic research and results at community level.…”
Section: Discussionsupporting
confidence: 81%
“…A qualitative study conducted among parents and caregivers of children and adolescents involved in an HIV-TB genomic study in Botswana reported that almost all participants wanted to receive their genetic results (Ralefala et al, 2021). However, satisfying the research participants’ demand for genomics and genetics analyses remains a debate among researchers and bioethicist communities on the African continent (Kasule et al, 2022; Kisiangani et al, 2022; Mwaka et al, 2021b; Ochieng et al, 2021b; Ralefala, Kasule et al, 2022). While these studies highlight the relevance and benefits of sharing genomics results with participants, a number of ethical concerns such as the possibility of misinterpreting these results, unnecessary worry to the participants and family members, and discrimination have been raised (Kaphingst et al, 2016; Yu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The increased demand for individual genomic and pharmacogenomic research results has sparked the need to develop locally contextualized guidelines for returning individual research results to participants (Kisiangani et al, 2022;Mwaka et al, 2021). Several guidelines have described when and how different kinds of results from genomic analyses should be returned (Burke et al, 2013;Green et al, 2013;Matimba et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, results from pharmacogenomic research have been associated with several ethical and social harms including discrimination (Sarwar, 2023), and loss of privacy and confidentiality (Kisiangani et al, 2022). Specific to communities infected with and affected by HIV, many PLHIV suffer depression (Abas et al, 2018; Bernard et al, 2017), despair (Dela Cruz et al, 2020), distress and fear (dela Cruz et al, 2016) after receiving results that reveal HIV infection.…”
Section: Introductionmentioning
confidence: 99%